Nurses' pain management practices for admitted patients at the Comprehensive specialized hospitals and its associated factors, a multi-center study - Legese Fekede; Worku Animaw Temesgen; Haileyesus Gedamu; Selamsew Kindie; Tola Getachew Bekele; Ambaw Abebaw; Aemiro Baymot; Mesfin Difer (BMC, 2023)
Abstract Background Pain is the most common challenge that most hospitalized patients complain of and is influenced by several patients, nurses, and institutional-related factors. Most studies in Ethiopia on pain were focused on surgical illnesses only. Objective To assess nurses' pain management practice and associated factors for admitted patients at Comprehensive Specialized Hospitals. Methods and materials : A multi-center institution-based cross-sectional study was conducted at the five randomly selected Comprehensive Specialized Hospitals of the Amhara region from May 01 to June 01, 2022. A multi-stage sampling method was employed to select a total of 430 nurses and patients for whom the nurses were responsible. Data were collected using standard self-administered, structured, and checklist questionnaires from nurses, patients, and patients' charts respectively. The modified Bloom's criteria categorized the overall practice as good, moderate, and poor. Data were checked, coded, and entered into Epi-Data version 4.6 and exported to SPSS version 25. An ordinal logistic regression model was applied, and variables with a p-value < 0.05 with a 95% CI in the multivariable analysis were considered significant. Results The study evaluated the pain management practices of 430 nurses and only a quarter had good pain management practices. Those nurses with first degrees and above education level (AOR = 2.282) and who attended in-service training (AOR = 2.465) were found to have significantly higher pain management practice. Expected though patients with painful procedures (AOR = 5.648) and who had severe pain (AOR = 2.573) were receiving better pain management practices from their nurse care provider. Nurses working in the institutions with a pain-free initiative focal person (AOR = 6.339) had higher pain management practices. Conclusion and recommendation : Overall, the majority of nurses had poor pain management practices. Higher educational levels, in-service training, and assigning a pain-free focal person had an impact on pain management services. Patients with higher pain levels and painful procedures were getting better attention. Hospital administrations need to provide due attention to the pain management of hospitalized patients by providing in-service training and educational opportunities to improve the capacity of nurses. Patients would be benefited considerably if hospitals focus on assigning focal persons for advocating regular pain management for admitted patients regardless of their pain level.